College enrollment over the business cycle: the role of supply constraints. Issue 1 (2nd January 2021) - Kim, Soobin
ABSTRACT: Studies on the cyclicality of higher education examine the relationship between variations in labor market conditions and changes in enrollment. While the majority of the existing literature implicitly assumes an elastic supply of enrollment, this study identifies institutions with supply constraints and investigates how those constraints have affected institutions' decisions on enrollment and how such effects vary across institution types. Findings indicate that, in the short run, capacity-constrained institutions experienced no changes in enrollment or academic qualifications for incoming students in response to increases in admission applications, whereas institutions without constraints responded by accepting more students, with lower SAT scores.